0208 Impact of Sleep Deprivation on Judgment of Afforded and Unafforded Opportunities. (27th April 2018) - LaGoy, A D; Sinnott, A M; Germain, A; Simpson, R J; Bower, J L; Alfano, C A; Connaboy, C
Abstract: Introduction: Correct attunement to affordances (action possibilities within an environment) is crucial for successful performance in occupations, such as astronauts, that are routinely exposed to system perturbations (i.e. sleep deprivation) that impact affordance judgment. The purpose of this study was to investigate affordance judgment performance under increasing sleep deprivation during 30-day NASA Human Exploration Research Analog missions. Methods: Sixteen participants completed a tablet-based perception-action coupling task (PACT) over days 22–25 of the missions. Normal sleep trials (BL, T2 and T3) were on day 22 (1800) and 24 (1200 and 1730) respectively. Sleep deprivation trials (T4-T6) were on day 25 (0430, 1200 and 1445) respectively. During PACT, participants judge whether virtual balls afford posting (i.e. can fit) through virtual apertures. After presentation of the pairing, participants respond using a virtual joystick to move the ball towards or away from the aperture. The ball-to-aperture size ratio ranges from 0.2–1.8 (afforded trials <1, unafforded trials >1). Response time (RT) defines the time from pairing presentation through response completion. A two-way repeated measures ANOVA was used to analyze the effect of time and affordance nature (comparing afforded and unafforded trials) on RT (α=0.05). Results: A significant main effect of time on RT was observed ( F (5, 75) = 7.974, p = 0.001). Subsequent analysis revealed significant differences between BL and T3 with T6. A significant main effect of affordance nature on RT was observed ( F (1, 15) = 17.554, p = 0.001). Subsequent analysis revealed significant differences at all timepoints. Afforded RT were slower than unafforded RT. No significant interaction effect was observed. Conclusion: Differences in performance between afforded and unafforded trials are maintained under increased sleep deprivation even as overall performance decreases. The implication of increased RT during afforded trials and under sleep deprivation conditions on behavioral risk and operational performance warrants further investigation. Support (If Any): None.